Job Safety Analysis Sebagai Penerapan Kesadaran Keselamatan dan Kesehatan Kerja Pada PT. Mega Sejahtera Sugan Di Jorong Sopang, Kecamatan Pangkalan Koto Baru, Kabupaten Lima Puluh Kota, Sumatera Barat - Luthfiandy Ramadhana; Rijal Abdullah (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT. Mega Sejahtera Sugan as one of the companies engaged in mining, is trying to capture the gaps in community needs that will support physical development activities carried out by the government. Estimated occurrence of work accidents at PT. Mega Sejahtera Sugan is the existence of rules about Occupational Safety and Health (K3) that have not been implemented properly. Awareness of employees in working that meets the Occupational Safety and Health (K3) method has not been achieved, for example the use of personal protective equipment (PPE) at work, Some methods in recognizing potential dangers of underground mining such as Job Safety Analysis have not been realized at PT. Mega Sejahtera Sugan. Some of the dangers in the mining environment are hot temperatures, lots of wildlife, watery roads, and no use of personal protective equipment. In controlling hazards some policies and guidelines are needed in the execution of work. The preparation of the Standard Operating Procedure is carried out by observing work processes directly so that each stage is able to be identified and identified the dangers. Standard Operating Procedure is made in writing and informed to all employees to comply with each stage of work and the policy.Keywords: Pengetahuan Karyawan, Sikap , Tindakan, Job Safety Analysis, Standard Operating Procedure